Exergaming in a Moving Virtual World to Train Vestibular Functions and Gait; a Proof-of-Concept-Study With Older Adults - Swanenburg, Jaap; Wild, Karin; Straumann, Dominik; Bruin, Eling D. de (Frontiers in Physiology, 2018)
Background: The use of Exergames designed to improve physical and cognitive functioning is relatively new in rehabilitation. As such, exergaming allows training of skills, handling of tools and procedures; however, these aspects are often not assessed for their potential before being adopted in clinical settings. This study aimed at exploring the effects of exergaming on vestibular functions and gait in healthy community dwelling older adults using a proof-of-concept study design registered under ClinicalTrials.gov NCT03160352. Methods: A pre-test-post-test one-group study design comprising 10 older adults (mean age of 73.5 ± 7.6 years, 4 male) investigated feasibility of eight exergaming training sessions (for a total of 160 min) and the effects on dynamic visual acuity (DVA), functional gait assessment (FGA), and extended timed get-up-and-go (ETGUG). The simulator sickness questionnaire (SQQ) and game scores were evaluated for feasibility of the intervention. Wilcoxon test and Cohen’s d (d) were chosen to test for differences and for effect size estimation. Results: Exergaming led to a significant improved DVA (z= –2.50, p = 0.01, d = 1.35) with nine out of ten participants improving. FGA also significantly improvement with a large effect size (z = –2.25, p = 0.02, d = 1.17). Specifically, component tasks such as walking with horizontal head turns (p=0.03), gait with a narrow base of support (p=0.03), ambulating backward (p=0.05) significantly improved. The ETGUG component task Gait initiation significantly improved (p=0.04). No change was found in gait speed and SQQ. The game scores of participants improved continuously during the course of the intervention for every game. Discussion: This proof-of-concept study suggests that the use of exergaming that requires active stepping movements and contains moving game projection is feasible and facilitates gaze stability during head movements in healthy community dwelling older adults. Aspects of functional gait and gait initiation also improve. Future research aiming at testing this exergaming intervention in patients suffering from vestibular impairments is warranted.